Self-Management Mentoring Model in Improving the Health Quality of Life of Productive Age Diabetics - Nurlatif, Rr. Vita; ‎ , Sumardiyono; Rahardjo, Setyo Sri (KnE Social Sciences, 2024)
Diabetes is a global epidemic, and failure to address it directly and effectively can lead to economic losses affecting countries in Asia and Africa. This systematic review was compiled to find a comprehensive self-management mentoring model by community health workers that have an impact on improving the quality of life. The search strategy for articles and data sources encompassed various electronic databases, including PubMed, Health evidence, Cochrane, Google Scholar, Web of Science, Publish and Perish. The search strategy utilized PICOT key ((((diabetes mellitus[Title/Abstract] OR diabetes management by peers [Title/Abstract])) AND (control[Title/Abstract] OR no[Title/Abstract])) AND (HQOL[Title/Abstract] OR QOL[Title/Abstract] OR HBA1C[Title/Abstract] OR blood pressure[Title/Abstract] OR Body mass index[Title/Abstract])) AND (week[Title/Abstract] OR month[Title/Abstract]) . Based on the searching results obtained 277 articles found, following screening, extraction, and Full-text review, 10 articles were synthesized, various models of self-management were obtained with peer assistance and community health workers, such as PBE, IBE, PBS, HE, HC, Model 5 healthy lifestyle, self-management with CHW mentoring for 3 months. COMP-DSMP Model for 3 months. Diabetes Online Model for diet & e-health for diabetics, “Blue Star Mobile Apps” Model, DSME DMT2 Model. The success of self-management is highly dependent on the amount of motivation of diabetes mellitus (DM) patients to improve their knowledge, attitudes, and practices in controlling and managing blood glucose control. Compliance with therapy, physical activity, control of sugar consumption, dietary management, stress management, and regulation of rest patterns are the keys to optimal quality of life for people with diabetes mellitus. Keywords: community health worker, health quality of life, self-management mentoring